Antifungal Peptides SmAPα1–21 and SmAPγ27–44 Designed from Different Loops of DefSm2-D Have Distinct Modes of Action - Iturralde, Micaela (2025)
Background: The use of antimicrobial peptides (AMPs) as biotechnological tools is an area of growing interest in the research that seeks to improve crop defense. SmAPα1–21 and SmAPγ27–44 were previously reported to inhibit Fusarium graminearum, permeabilize the plasma membrane and induce cytoplasmic disorganization. To exert its activity, SmAPα1–21 initially enters through the basal and apical cells of F. graminearum conidia and then displays a general but non-homogeneous distribution in the cytoplasm of all conidial cells, in contrast. Methods: We analyzed, focusing on membrane interaction, the mode of action of SmAPγ27–44, a peptide based on the γ-core of defensins DefSm2-D and DefSm3, and SmAPα1–21, based on the α-core of DefSm2-D. Additionally, we compared the behavior of SmAPα1–21 with that of SmAP3α1–21 based on DefSm3 but with no activity against F. graminearum. Results: In this study, we showed that SmAPγ27–44 enters the cells with discrete intracellular localization. Furthermore, both peptides disrupted the plasma membrane, but with different modes of action. When large unilamellar liposomes (LUVs) containing phosphatidic acid and ergosterol were used as a filamentous fungal plasma membrane model, SmAPγ27–44 strongly induced aggregation concomitantly with the solubilization of the liposomes and showed the maximal insertion of its tryptophan moiety into the membrane’s hydrophobic interior. In comparison, SmAPα1–21 showed a high effect on the ζ potential of anionic vesicles, vesicle aggregation capacity after reaching a concentration threshold, and moderate transfer of tryptophan to the membrane. SmAP3α1–21, on the other hand, showed poor superficial adsorption to liposomes. Conclusions: In view of our results, a cell penetration peptide-like effect was pictured for the γ-core defensin-derived peptide and a classical AMP action was observed for the α-core defensin-derived one.